The mystery of my fathers & other short stories - Ngcobo, Patrick Lucky Msawenkosi (Rhodes University, 2026)
My thesis comprises a collection of short stories that take a leaf out of Jose Saramago’s great literary works, particularly Blindness, where the power of the human spirit triumphs in the face of adversity. Novelists like Yuri Herrera who tactically bring together the scattered fragments of Makina’s life in the novel, Signs Preceding the End of the World, so superbly have also inspired the construction of the pieces. In Cain, Saramago demonstrates that a conversation with a "super being" is possible, the same is done here. I challenge traditional norms and institutions such as the church and government. Through personal reflections, I also explore themes of love for one another, as well as the self. My short stories offer a series of perspectives across pertinent discussion points within the socio-political sphere.
Keywords: Creative writing (Higher education) (http://id.loc.gov/authorities/subjects/sh85033849); Short stories, South African (English)--21st century (http://id.loc.gov/authorities/subjects/sh85121941); Diaries--Authorship (http://id.loc.gov/authorities/subjects/sh87000054); Books--Reviews (http://id.loc.gov/authorities/subjects/sh85015752); Creative Writing